Simulation-based education, training and assessment in dentistry at the University of Health Sciences, Cambodia - Tong Leang
This study is a cross-sectional survey to describe the current use, priority needs, and perception of fifth year dental students on simulation based teaching in the Faculty of Dentistry, University of Health Sciences, Kingdom of Cambodia The Objectives of this study are to 1) describe in a systematic way the current use of simulation based education training (SBET) for undergraduate students in the preclinical years at the Faculty of Dentistry, UHS; 2) identify priority needs of implementing an SBET at the Faculty of Dentistry UHS; 3) explore the perceptions of students' experience with SBET at the end of preclinical year at the Faculty of Dentistry, UHS. A total of 26 faculty members and 85 students participated in this study. Results showed that only 23% of clinical laboratory faculty members are trained in the use of SBET while the overall use of SBET is limited to use of tooth models and student patient simulators. Review of records, direct observations and field interviews revealed that SBET is not fully integrated in current clinical laboratory curricula and syllabi. Faculty members identified as their priority need for improving the quality of dental education the acquisition of high technology tooth mannequins and training in the use and integration of SBET in curricula and syllabi. In terms of students perceptions of SBET, 86 respondents gave a positive rating (Mean = 2.05) of their experience in SBET limited as it is. In conclusion, the results provided an objective look at simulation-based education training in dentistry providing important information needed to identify priority areas for improving the overall quality of clinical skills training. These results further demonstrated that even though SBET is limited to use of tooth mannequin and student patient simulators, students appreciate the opportunity to practice repeatedly in a risk free learning setting.